Hypoxia and Hypoxia-Inducible factors in Breast Cancer: Targeting Breast Cancer Stem Cells - Wasi Alam, Muhammad (My University, 2012)
Background: Breast cancer is one of the most common cancers in western women. The cancer stem cell hypothesis say that in tumors, including breast cancer, only a small subpopulation of cells called cancer stem cells (CSCs), can induce invasion and metastasis. These CSCs shows resistance to radiation therapy and some chemotherapy and later on recurrence may take place. Hypoxia has been proposed to be one of the driving forces of CSCs. Hypoxia is associated with poor prognosis in cancer. Cell adaptation to hypoxic conditions is mainly directed by the activity of two hypoxia induced transcription factors, HIF-1a and HIF-2a that are accumulated under low oxygen conditions. Epithelial-to-mesenchymal-transition is a prerequisite for tumor spread and has been proposed to give rise to cancer stem cells. Aim: • To study if the frequency of the proposed CSC population is altered by oxygen conditions. – Optimize method and study in cell lines – Transfer to primary cells from tumors and secondary sites i.e. pleural effusions • To set up and optimize method for cell sorting of CSCs based on at first CD44/CD24 phenotype. • To compare the phenotype of stem and non-stem cancer cells (first cell lines later primary cells). Methods: Culture cells in hypoxia to mimic in vivo conditions and then FACS analysis was performed for the expression of CD markers (CD44+/CD24- and E-cadherin) and Aldefluor-activity assay. Expressions of HIFs are monitored by western blotting and their transcriptional activity by QPCR. Results and Conclusions: We found with FACS that, a population at hypoxia a population of MCF-7 cells showed loss of E-cadherin i.e. traits of epithelial-to-mesenchymal-transition. To find out whether these cells are cancer stem cells, we will sort them out and inject into the NOD-SCID mice.
Keywords: Biologiska vetenskaper; Livsvetenskaper; Biological Sciences; Life Science